Involvement of the Interaction of Afadin with ZO-1 in the Formation of Tight Junctions in Madin-Darby Canine Kidney Cells - Ooshio, Takako (American Society for Biochemistry and Molecular Biology, 2010)
Tight junctions (TJs) and adherens junctions (AJs) are major junctional apparatuses in epithelial cells. Claudins and junctional adhesion molecules (JAMs) are major cell adhesion molecules (CAMs) at TJs, whereas cadherins and nectins are major CAMs at AJs. Claudins and JAMs are associated with ZO proteins, whereas cadherins are associated with β- and α-catenins, and nectins are associated with afadin. We previously showed that nectins first form cell-cell adhesions where the cadherin-catenin complex is recruited to form AJs, followed by the recruitment of the JAM-ZO and claudin-ZO complexes to the apical side of AJs to form TJs. It is not fully understood how TJ components are recruited to the apical side of AJs. We studied the roles of afadin and ZO-1 in the formation of TJs in Madin-Darby canine kidney (MDCK) cells. Before the formation of TJs, ZO-1 interacted with afadin through the two proline-rich regions of afadin and the SH3 domain of ZO-1. During and after the formation of TJs, ZO-1 dissociated from afadin and associated with JAM-A. Knockdown of afadin impaired the formation of both AJs and TJs in MDCK cells, whereas knockdown of ZO-1 impaired the formation of TJs, but not AJs. Re-expression of full-length afadin restored the formation of both AJs and TJs in afadin-knockdown MDCK cells, whereas re-expression of afadin-ΔPR1–2, which is incapable of binding to ZO-1, restored the formation of AJs, but not TJs. These results indicate that the transient interaction of afadin with ZO-1 is necessary for the formation of TJs in MDCK cells.